The combined transarterial and transvenous onyx embolization of dural arteriovenous fistula of hypoglossal canal via the external jugular vein and facial vein: A case report - Yang, Biao; Ren, Yeqing; Wu, Yongqiang; Zhang, Wenju; Sun, Yanqi; Guo, Xiaolong; Lv, Ming; Guo, Geng (Frontiers in Surgery, 2023)
Dural arteriovenous fistulas of hypoglossal canal (HCDAVFs) involving anterior condylar confluence (ACC) and/or anterior condylar vein (ACV) are infrequent. Although transvenous embolization through internal jugular vein (IJV) is the preferred option treatment for type I and II fistulas, it is challenging in these cases if IJV is unavailable in these cases. Here we report a rare case of HCDAVF in which the most common transvenous embolization access via IJV was not available. The patient underwent combined transarterial and transvenous Onyx embolization. Transarterial embolization (TAE) aimed at controlling the arterial inflow and subsequently TVE was performed via the external jugular vein (EJV), the facial vein, the ophthalmic vein, the cavernous sinus, inferior petrosal sinus (IPS) and ultimately to the fistula pouch. Complete obliteration of the HCDAVF was achieved without complications. We suggest that transvenous embolization (TVE) via the EJV and the facial vein can be effective in cases where trans-IJV is not possible.